PEMETAAN AWAL KEBERLANJUTAN IMPLEMENTASI PEMBELAJARAN KODING DAN KECERDASAN ARTIFISIAL (KKA) PADA JENJANG SMP DI KABUPATEN KARANGASEM - Ida Ayu Putu Febri Imawati; Ni Ketut Erawati; I Wayan Dika (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
The forms of implementation of Coding and Artificial Intelligence (KKA in Indonesian) learning may include integration with existing subjects, implementation as a compulsory or stand-alone subject, and implementation through extracurricular activities. This community service activity aims to conduct an initial mapping of the forms and sustainability of KKA learning implementation at the junior secondary school level in Karangasem Regency after the KKA mentoring activity was carried out. Informal communication and confirmation with teachers or school representatives are simple techniques for conducting the initial mapping. The information collected was limited only to the forms of KKA implementation in the first and second semesters of the 2025/2026 academic year. The forms of implementation were divided into three categories, namely integration with subjects, compulsory learning, and extracurricular activities. The data obtained were recapitulated and analyzed descriptively using frequencies and percentages. The results of the initial mapping of 14 schools showed that 12 schools, or 85.71%, implemented KKA in an integrated manner with subjects, one school, or 7.14%, implemented KKA as compulsory learning, and one school, or 7.14%, implemented it through extracurricular activities. The reported forms of implementation did not change between the first and second semesters.